Long-term follow-up in common variable immunodeficiency: the pediatric-onset and adult-onset landscape - Carrabba, Maria; Salvi, Marco; Baselli, Lucia Augusta; Serafino, Serena; Zarantonello, Marina; Trombetta, Elena; Pietrogrande, Maria Cristina; Fabio, Giovanna; Dellepiane, Rosa Maria (Frontiers in Pediatrics, 2023)
Introduction The primary aim of this study is to investigate the evolution of the clinical and laboratory characteristics along the time in a longitudinal cohort of pediatric-onset and adult-onset Common Variable Immunodeficiency (CVID) patients in order to identify early predictive features of disease and immune dysregulation complications. Methods This is a retrospective-prospective monocentric longitudinal study, lasted since 1984 until the end of 2021. The data of pediatric-onset vs adult-onset patients have been compared for immunological features and for infectious and non-infectious complications assessed at diagnosis and at follow-up. Results Seventy-three CVID patients have been enrolled, with a mean of 10.0 years (SD± 8.17) of prospective follow-up. At diagnosis, infections were observed in 89.0% patients, and immune dysregulation in 42.5% patients. At diagnosis, 38.6% of pediatric-onset and 20.7% of adult-onset patients presented with only infections. Polyclonal lymphoid proliferation (62.1%) and autoimmunity (51.7%) were more prevalent in the adult-onset than in the pediatric-onset group (polyclonal lymphoid proliferation 52.3% and autoimmunity 31.8%, respectively). Enteropathy was present in 9.1% of pediatric-onset and in 17.2% of adult-onset patients. The prevalence of polyclonal lymphoid proliferation increased during follow up more in pediatric-onset patients (diagnosis 52.3% - follow up 72.7%) than adult-onset ones (diagnosis 62.1% - follow up 72.7%). The cumulative risk to develop immune dysregulation increases according to the time of disease and to the time of diagnostic delay. At the same age, pediatric-onset patients have roughly the double risk to have a complication due to immune dysregulation than adult-onset patients, and it increases with the increasing of diagnostic delay. The analysis of lymphocytes subsets in the pediatric-onset group showed that CD21low Bcells at diagnosis may be a reliable prognostic marker for the development of immune dysregulation during follow-up, as the ROC curve analysis showed (AUC=0.796). In the adult-onset group, the percentage of transitional B cells measured at diagnosis showed a significant accuracy (ROC AUC=0.625) in identifying patients at risk of developing immune dysregulation. Discussion The longitudinal evaluation of lymphocytes subsets combined with clinical phenotype can improve the prediction of lymphoid proliferation and allow experts to achieve early detection and better management of such complexed disorder.